2020
DOI: 10.53841/bpssex.2020.11.1.9
|View full text |Cite
|
Sign up to set email alerts
|

LGBTIA-related articles within British Psychological Society Journals: A review of the literature from 1941-2017

Abstract: This article identifies the quantity and diversity of lesbian, gay, bisexual, trans, intersex and asexual (LGBTIA) related journal articles published within the official British Psychological Society (BPS) journals. A systematic search of BPS journals was conducted using the BPS/Wiley search engine PsychSource. The search was conducted on 1 January 2018 and no timeframe was set for the search. Sixty-nine articles were identified across the BPS journals between 1941–2017. Until the end of the 1970s content focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Psychology in the 1970s (Hegarty, 2018a). However, it was not until the 1980s that such shifts were evident in Britain (Jowett, 2018a). For example, Schofield had a degree in Psychology and was deeply interested in the causes and possible treatments for homosexuality, but his work did not find a place at this time in British Psychology.…”
Section: S To 1960s: the Law And The Psychologist As Expertmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychology in the 1970s (Hegarty, 2018a). However, it was not until the 1980s that such shifts were evident in Britain (Jowett, 2018a). For example, Schofield had a degree in Psychology and was deeply interested in the causes and possible treatments for homosexuality, but his work did not find a place at this time in British Psychology.…”
Section: S To 1960s: the Law And The Psychologist As Expertmentioning
confidence: 99%
“…British Psychology began to increasingly recognize non-normative sex, gender, and sexuality as social rather than individual concerns. Jowett (2018a) found that sexuality became an object of study for social Psychology rather than for medical Psychology in British Psychology journals in the 1980s. This came about in the context of HIV/AIDS, which was conceptualized in public and professional discourses as both social and individual.…”
Section: S To 1998: Social Concerns and Institutional Recognitionmentioning
confidence: 99%